EFEKTIVITAS PENAMBAHAN SERBUK BIJI ASAM JAWA (Tamarindus indica) DALAM MENURUNKAN TSS PADA LIMBAH CAIR TAHU DI KECAMATAN PONTIANAK UTARA - Irawan, Hery; Rochmawati, Rochmawati; Asmadi, Asmadi (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2014)
Tofu liquid waste contains suspended and dissolved solids. Suspended solid may reduce sunlight penetrasion into the water so that it can affect the regeration of oxygen and photosynthesis.nin addition, deposition and decomposition of organic materials can reduce the quality of the water that would influence turbidity of the water. The problem formulation of this study was the effectiviness of additional tamarind seed powder in lowering the total suspended solid levels in tofu wastewater. This study is aimed at discovering the effectiviness of additional tamarind seed powder in lowering the total suspended solid levels in tofu wastewater, measuring the value of total suspended solid before and after added by the tamarind seed fowder, and measuring the dose effectivity of 300 mg/l, 400 mg/l, 500 mg/l, 600 mg/l and 700 mg/l of tamarind seed powder in lowering the total suspended solid levels in tofu wastewater.A quasi experimental design and one group pretest posttest design were carried out in this study. The samples were 30 tofu wastewater. The jartest was conducted at laboratory of Environmental Health Politechnique. While the saple was analyzed at Laboratory of Soil Quality and Health of Agriculture Faculty of Tanjungpura University.The study revealed that there was a meaningful reduction of total suspended solid level before and after the treatment. The value of total suspended solid level before the treatment was 2937,6 mg/l. while the total suspended solid level after the treatment decreased to 1401,6 mg/l. Hence, the optimum dose of tamarind seed powder in lowering total suspended solid levels in tofu wastewater was 600 mg/l with the effectivity level of 54,104%.Keywords : Tofu wastewater, tamarind seed powder, Total Suspended Solid